SOME UNSETTLED PROBLEMS OF INCOME. - Bowers, Russell (The Accounting Review, 1940)
Abstract The article focuses on some unsettled problems of income. Much has been written about income for tax purposes. Some writers have been concerned with concepts and definitions; some have been devoted to the more detailed problems of measurement. A study of the concepts and definitions shows a great variety of opinions among writers from such important countries as the U.S., England, France, Germany and Italy. Concepts of taxable income, which have been presented often come from writers in political economy who have in view some special social or national fiscal policy. The concept sometimes has an ethical flavor other than the capacity of the individual to pay. Types of definition vary greatly in fundamental content. At one extreme is the idea that income is determined by the disposition made of the form in which it is embodied while at the other extreme is the idea that there is income only after there has been ample deduction for both consumption and capital maintenance. Concepts applied vary with expediency social and political ends, or other consideration not based on individual capacity. There is often unfair discrimination as between individuals whose composite respective income situations might in fact be similar.